2009
DOI: 10.1083/jcb.200812060
|View full text |Cite
|
Sign up to set email alerts
|

Acetylation and activation of STAT3 mediated by nuclear translocation of CD44

Abstract: Expression of the type I transmembrane glycoprotein CD44 has recently been recognized as a signature for cancer stem cells. In this study, we demonstrate that CD44, once engaged, is internalized and translocated to the nucleus, where it binds to various promoters, including that of cyclin D1, leading to cell fate change through transcriptional reprogramming. In regulating cyclin D1 expression, the internalized CD44 forms a complex with STAT3 and p300 (acetyltransferase), eliciting STAT3 acetylation at lysine 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
117
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(124 citation statements)
references
References 28 publications
5
117
0
2
Order By: Relevance
“…We also show that mutant CD44, lacking the signal peptide required for membrane localization, has a diminished ability to localize to the nucleus. Ligation of CD44 by osteopontin or Hermes-3 antibody promotes its nuclear localization (22). We show here that hyaluronic acid binding does not influence nuclear localization, as nuclear import of the R41A mutant is not impaired.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…We also show that mutant CD44, lacking the signal peptide required for membrane localization, has a diminished ability to localize to the nucleus. Ligation of CD44 by osteopontin or Hermes-3 antibody promotes its nuclear localization (22). We show here that hyaluronic acid binding does not influence nuclear localization, as nuclear import of the R41A mutant is not impaired.…”
Section: Discussionmentioning
confidence: 59%
“…Previous work (22) has shown that ligation of cell surface CD44 by antibody or osteopontin can enhance its nuclear translocation. We therefore asked whether hyaluronic acid binding could play the same role in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…In non-small cell lung cancer, hyaluronan promotes the CD44-dependent association of the stem cell marker NANOG with both the phosphorylated and the unphosphorylated forms of STAT3, resulting in chemo-resistance that depends upon induced expression of the microRNA miR-21 (28). Lee et al (19) have demonstrated that the transmembrane glycoprotein CD44, recently recognized to be a signature of cancer stem cells, is internalized following its binding to osteopontin or Hermes 3, an anti-CD44 antibody. In the nucleus, CD44, in complex with STAT3 and p300, activates the CCND1 promoter, thus stimulating cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with resveratrol (a histone deacetylase activator) significantly decreases the STAT3 K685 acetylation followed by increase in ERα expression at both protein and mRNA level as well as sensitizes the TNBC cells to tamoxifen-induced cell death [43]. Acetylated K685 STAT3 is also known to interact with CD44 and regulate transcription of cyclin D1 gene in case of gastric cancer [81]. Acetylated STAT3 is also known to regulate the non-canonical NF-κB signaling pathway.…”
Section: Ps727 Phosphorylation and K685 Acetylation Of Stat3: The Nonmentioning
confidence: 99%